Platelet Counts and Coagulation Tests Prior to Neuraxial Anesthesia in Patients With Preeclampsia: A Retrospective Analysis. (September 2013) - Sultan, Pervez; Butwick, Alexander
This retrospective, descriptive study aimed to assess hematologic testing practices in 100 patients with preeclampsia undergoing neuraxial blockade (NB). Prior to NB, platelet (PLT) count was performed in 61 (98%) of 62 women in labor and in 37 (97%) of 38 women undergoing cesarean delivery (CD). No patients had a pre-NB PLT count <70 × 10 9 /L. Pre-NB tests for prothrombin time (PT) and activated partial thromboplastin time (APTT) were less common and varied among laboring patients (15 [24%] of 62) and patients prior to CD (18 [47%] of 38). Prior to NB, PT and APTT values were within normal limits in all patients. The time intervals between laboratory testing and NB ranged from <2 to >12 hours. The lack of consistency in pre-NB coagulation testing and the variable time intervals between laboratory tests and NB may be due to a lack of consensus among anesthesiologists for determining "safe" hemostatic conditions for NB placement in patients with preeclampsia.